2020
DOI: 10.3390/ijerph17228305
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Psychosocial Interventions in Age-Friendly Communities and Active Ageing: A Systematic Review

Abstract: Background: The academic literature contains little information regarding the interventions that create age-friendly cities and communities in order to promote active ageing. Objectives: A systematic review was carried out to determine the available empirical evidence in relation to the characteristics, content and effectiveness of interventions aimed at improving environmental and psychosocial risk factors for older people, from the perspective of age-friendly communities and the promotion of active ageing. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 108 publications
0
25
0
Order By: Relevance
“…In this study, no homogeneous pattern has been observed according to the two large pro le groups, such that both pro le I and V subjects reside in large urban and metropolitan areas, while the remaining ones do so in smaller cities. In any case, the trend towards urbanisation has led to the development of a speci c city friendliness programme in order to optimise the living conditions and quality of life of older adults (30,126).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, no homogeneous pattern has been observed according to the two large pro le groups, such that both pro le I and V subjects reside in large urban and metropolitan areas, while the remaining ones do so in smaller cities. In any case, the trend towards urbanisation has led to the development of a speci c city friendliness programme in order to optimise the living conditions and quality of life of older adults (30,126).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Health is a widely studied pillar (20), which can be used as an enabling factor for AA (21,22) or as an outcome consistent with an active way of ageing (23)(24)(25)(26). The second pillar, Participation, tends to be very widely represented in any of its meanings, from the most general, engaging in activities (27)(28)(29)(30), to other more speci c, but highly relevant, activities such as volunteer work (31)(32)(33)(34)(35)(36). Many of these studies refer to participation to highlight its effects on health, well-being and quality of life.…”
mentioning
confidence: 99%
“…A total of 32 systematic reviews (25.8%) reported on urban system determinants of health categorised as spatial planning (17 studies); housing system (11 studies): and ecosystems (four studies) (Table 3; and see Table S3 in the supplemental data online). Physical activity (Nordbø et al 2018;McCrorie et al 2014;Durand et al 2011;Rocha et al 2019), mental health (Gong et al 2016, including the health of children and the elderly (Sánchez-González et al 2020;Kabisch et al 2017), and morbidity and mortality (Salgado et al 2020) Air pollution, noise, UHI, green and blue space (Salgado et al 2020;Kabisch et al 2017;Rocha et al 2019) Housing system Vulnerability (e.g. housing status, insecurity and instability; social housing) Physical health, mental health and health-related behaviours (Vásquez-Vera et al 2017;Downing 2016;Tsai 2015;Singh et al 2019;Davey et al 2020;Aidala et al 2016), as well as healthrelated social outcomes (Aubry et al 2020;Tanner et al 2013) Energy access and fuel poverty (Tanner et al 2013) Policy (e.g.…”
Section: Urban System Determinants Of Health (32 Studies)mentioning
confidence: 99%
“…physical inactivity), injury and mental health. More specifically, these studies focused on nature-based approaches (Kabisch et al 2017), age-friendly infrastructure for the elderly or children (Sánchez-González et al 2020;Nordbø et al 2018), and smart city technologies (Rocha et al 2019). Strategic planning and smart growth approaches were also included (McCrorie et al 2014;Durand et al 2011;Gong et al 2016;Salgado et al 2020).…”
Section: Spatial Planningmentioning
confidence: 99%
“…Studies investigating social inclusion interventions for older adults and people with disabilities exist, but calls to improve this evidence base have been made [12]. Systematic reviews have found that interventions to improve participation and inclusion are substantially varied in their focus and that there is limited evidence of long-term effectiveness, including for technological interventions [13], occupational therapy interventions [14], and environmental and psychosocial interventions connected to age-friendly communities [15].…”
Section: Introduction 1social Participation As a Component Of Health ...mentioning
confidence: 99%